2003
DOI: 10.1021/ic034333j
|View full text |Cite
|
Sign up to set email alerts
|

Chelating Agents Related to Ethylenediamine Bis(2-hydroxyphenyl)acetic Acid (EDDHA):  Synthesis, Characterization, and Equilibrium Studies of the Free Ligands and Their Mg2+, Ca2+, Cu2+, and Fe3+ Chelates

Abstract: Iron chelates such as ethylenediamine-N,N'-bis(2-hydroxyphenyl)acetic acid (EDDHA) and their analogues are the most efficient soil fertilizers to treat iron chlorosis in plants growing in calcareous soils. EDDHA, EDDH4MA (ethylenediamine-N,N'-bis(2-hydroxy-4-methylphenyl)acetic acid), and EDDCHA (ethylenediamine-N,N'-bis(2-hydroxy-5-carboxyphenyl)acetic acid) are allowed by the European directive, but also EDDHSA (ethylenediamine-N,N'-bis(2-hydroxy-5-sulfonylphenyl)acetic acid) and EDDH5MA (ethylenediamine-N,N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
133
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(143 citation statements)
references
References 39 publications
(62 reference statements)
10
133
0
Order By: Relevance
“…These studies require knowledge of the previous chemical characterisation of the ligands, including their protonation and stability constants with metals. This type of modeling has been already applied to study the stability of several Fe chelates (Yunta et al, 2003b;López-Rayo et al, 2009), showing a good correlation between the modeling results and their behaviour in agronomics conditions. Also, different tests have been proposed López-Rayo et al, 2009 and …”
Section: +mentioning
confidence: 92%
See 2 more Smart Citations
“…These studies require knowledge of the previous chemical characterisation of the ligands, including their protonation and stability constants with metals. This type of modeling has been already applied to study the stability of several Fe chelates (Yunta et al, 2003b;López-Rayo et al, 2009), showing a good correlation between the modeling results and their behaviour in agronomics conditions. Also, different tests have been proposed López-Rayo et al, 2009 and …”
Section: +mentioning
confidence: 92%
“…Most of the stability constants of the chelates with Fe, Mn and Zn were obtained from the literature (Yunta et al,201X) 2+ were determined using the potentiometric method described by Yunta et al(2003b) since they have not been reported. This method consists of the titration with HCl 0.05 M solution of the chelate formed with metal:ligand 1:1 ratio from pH 10 to pH 2.5 at 25ºC under N 2 atmosphere.…”
Section: Stability Of Fe Mn and Zn Fertiliser Formulations In Aqueoumentioning
confidence: 99%
See 1 more Smart Citation
“…These two chelators differ significantly in their effectiveness at binding iron, with DFO being the more powerful iron chelator (41,59). In aqueous solution, enterobactin could spontaneously break down into the trimers, dimers, and monomers of dihydroxybenzoyl serine (DHBS) (14,26).…”
Section: Fig 2 Operon Mapping By Rt-pcr Analysis Of Iron-andmentioning
confidence: 99%
“…To test the effect of desferrioxamine B on a natural microbial population, complexed to DFB in a 1:2 ratio was added to seawater at concentrations of 400:800 nM, (Yunta et al, 2003) but photolabile Fe complexes and is known to induce Fe limitation in Synechococcus (Chadd et al, 1996).…”
Section: The Effect Of Desferrioxamine B On An Atlantic Microbial Popmentioning
confidence: 99%